IMPLEMENTASI PEMBELAJARAN MENGGUNAKAN MODEL KOOPERATIF TIPE STAD BERBANTUAN MEDIA QUIZIZZ UNTUK UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI HUKUM NEWTON KELAS X SMA - Karismara Olivya Afiva Jothy; Zuhdi Ma’aruf; Muhammad Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning outcomes are results that must be achieved after the learning process takes place. One aspect of learning outcomes is cognitive learning outcomes. The purpose of this study was to determine the effect of the application of the STAD type cooperative learning model assisted by Quizizz media on students' cognitive learning outcomes. The type of research used is experimental research with a quasi-experimental design "Nonequivalent control group design" with a "posttest only control group design" model. The population of this study were all students of class X IPA at SMA Negeri 1 Tambang for the academic year 2021/2022 with a sample of 59 students consisting of class X IPA 1 as a control class with 31 students and class X IPA 2 as a experimental class with 28 students. The data collection instrument was in the form of a cognitive learning outcome test for Newton's law class X which consisted of 10 multiple choice questions and 5 essay questions. The data analysis used was descriptive analysis through student absorption and inferential analysis through normality test, homogeneity test and Mann Whitney test with the help of SPSS version 22. The results showed that the absorption of students in the experimental class was better than the control class and there were significant differences in the results students cognitive learning between the experimental class that applies the STAD type cooperative model assisted by the quizizz media and the control class that applies the conventional learning model.Keywords: Student Learning Outcome, cognitif Student Learning Outcome, Cooperative Learning, STAD, Quizizz, Newton Law’s